Ship Bow Wings with Application to Trim and Resistance Control in Calm Water and in Waves - Dimitris Ntouras; George Papadakis; Kostas Belibassakis (Journal of Marine Science and Engineering, 2022)
Flapping foils for augmenting thrust production have drawn attention as a means of assisting ship propulsion in waves due to their high efficiency rate compared to traditional screw propellers. However, they can also offer substantial resistance reduction when used as stabilizers. In this work, the aim is to investigate the feasibility of a symbiotic concept combining the ship’s propeller with a foil arranged at the ship’s bow at a fixed position operating as a trim-pitch stabilizer. The work presents results obtained from experiments conducted in the towing tank of the Laboratory of Ship and Marine Hydrodynamics of the National Technical University of Athens (LMSH NTUA), as well as results from an in-house CFD solver. The test cases focused on the resistance and the dynamic behavior of the wing–vessel configuration in calm water conditions and in head waves. All results were compared against the performance of a bare hull (without foil). The findings of this work are based both on numerical and experimental data and indicate that a bow wing in static mode can be used for trim-control of a vessel by altering the angle of attack leading to a possible drop in wave resistance both in calm water and in waves. In the latter case, utilizing the wing in head waves results in a significant reduction in the pitching and heaving responses of the vessel, which may lead to substantial enhancement of the propulsion performance.